1998
DOI: 10.1539/joh.40.83
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Status of Some Ethiopian State Farm Workers Exposed to Organophosphate Pesticides

Abstract: Cholinesterase Status of Some Ethiopian State Farm Workers Exposed to Organophosphate Pesticides : Kibruyisfa Lakew, et al. Occupational Safety and Health Division, Region 14 Labour and Social Affairs Bureau—The effects of organophosphate (OP) pesticide exposure on cholinesterase (ChE) activities were assessed in relation to occupational factors by studying 430 pest control workers from three state farms and 161 comparable controls. Plasma cholinesterase (PChE) and erythrocyte cholinesterase (AChE) activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(3 reference statements)
0
4
0
1
Order By: Relevance
“…2003) to ward off mosquitoes and other domestic insects though it is difficult to know their contribution in the development of resistance. The contribution of pesticides used in agriculture to the development of resistance in the vector population cannot be overlooked as there are reports that DDT and different organophosphates (Abate 1996; Lakew & Mekonnen 1998; Amera & Abate 2008) and possibly pyrethroids are used to control agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…2003) to ward off mosquitoes and other domestic insects though it is difficult to know their contribution in the development of resistance. The contribution of pesticides used in agriculture to the development of resistance in the vector population cannot be overlooked as there are reports that DDT and different organophosphates (Abate 1996; Lakew & Mekonnen 1998; Amera & Abate 2008) and possibly pyrethroids are used to control agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…22) Other investigators also studied ChE activities among pest-control workers who used chlorpyrifos occupationally, and the result showed that mean PChE and AChE activities after pesticide exposure were significantly lower than pre-exposure values (pϽ0.05); 16 and 40% of the pestcontrol workers had PChE and AChE levels below 50% of the pre-exposure values, respectively. 23) We propose that farm-worker exposure to OPs, such as chlorpyrifos, may be monitored by measuring the activity of plasma cholinesterase (PChE), but not AChE. Therefore, from a biological point of view, it may be used as a potential biomarker in monitoring pesticide exposure in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Farm workers are at risk of exposure to pesticides during mixing, loading and spraying of pesticides and during the assessment of pests [1,2]. Organophosphate and carbamate pesticides inhibit the action of acetyl cholinesterase, the enzyme used to deactivate the nerve transmitter acetylcholine at the nerve endings.…”
Section: Introductionmentioning
confidence: 99%